Lift-off of GaN-based LED membranes from Si substrate through electrochemical etching. (1st August 2022) - Jiang, Tianhao; Wang, Jian; Liu, Jiaqi; Feng, Meixin; Yan, Shumeng; Chen, Wen; Sun, Qian; Yang, Hui
Abstract: Semiconductor nano-membranes provide a new way to develop optical devices with better performance. Herein, we report a fabrication method of GaN-based LED membranes with a complete device structure including contact metals from Si substrate by using electrochemical etching of highly conductive AlN/Si interface, which is often naturally formed in GaN-on-Si materials. Photoluminescence and Raman scattering spectra show that the internal stress after the lift-off was effectively lightened with 1.45 GPa. Electrical measurement results show that both the leakage current and series resistance were largely decreased, and strong and uniform electroluminescence further proved the well-preserved whole structure.